Violencia física y psicológica contra la mujer embarazada - Medina Meza, Diana Patricia; Martínez Salgado, Juan Camilo; Suárez Rodrígez, Juan Carlos; Castro Naranjo, Luis Javier; Muriel Perea, Yina Yuliza; Obando, Marta Nelly (Investigación y Educación en Enfermería, 2013)
.